Psychological impact on near relatives of patients admitted in intensive care unit - Kripalani, Sanjay (International Journal of Research in Medical Sciences, 2022)
Background: It is recognized that ICU patients are exposed to massive stresses both from their life-threatening illness and the necessary intensive medical procedures they are subjected to. These stresses may lead to psychological problems like depression, anxiety and post-traumatic stress disorder. However, the psychological demands and impact of the ICU on the near relatives of these patients are often not appreciated. We aimed to determine the prevalence of anxiety and depression and the influence of ICU specific interventions on the development of psychological symptoms in relatives of ICU patients. Methods: This prospective, questionnaire-based observational study was conducted on all consenting near relatives of patients on admission in the intensive care unit during the study period. The Hospital Anxiety and Depression Scale and the General Health Questionnaire were used to determine the presence of psychological disorders during this study. Results: In this study, GHQ demonstrated a 72.5% prevalence of psychological illness in near relatives of ICU patients. The prevalence of psychological illness using Hospital Anxiety and Depression Scale (HADS) was 56.3% on the anxiety scale and 55% on the depression scale. Conclusions: Critical care can result in the development of psychological disorders among near relatives of ICU patients. Intensive care physicians need to pay more attention to their care’s impact on the psychological health of their patients’ near relatives.